Developing novel hybrid reefs to provide both wave energy reduction and opportunities for ecological restoration - Benjamin K. Norris; Borja G. Reguero; Camila Gaido-Lasserre; David Gutierrez-Barcelo; Joseph Bartolai; Michael A. Yukish; Landolf Rhode-Barbarigos; Brian K. Haus; Taylor Squires; Gabriel Barajas Ojeda; Maria Maza; Javier L. Lara; et al. (Coastal Engineering, 2026)

Geochemistry of the 2022 Mauna Loa eruption: a comparison with earlier historical summit reservoir eruptions, with implications for magma supply and recharge - J. Michael Rhodes; Frank A. Trusdell; Kendra J. Lynn; Drew T. Downs; Michael Vollinger (Bulletin of Volcanology, 2026)

Utilizing Exhaled Breath and Skin Microbiomes in Assessments of At‐Risk Killer Whales ( Orcinus orca ) - Linda D. Rhodes; Hendrik H. Nollens; Sheila J. Thornton; Candice K. Emmons; James Sheppard; Michael S. Felice; Todd R. Robeck; M. Bradley Hanson (Marine Mammal Science, 2026)
For at‐risk populations of killer whales ( Orcinus orca ), biological samples can offer information about individual animal status. We hypothesized that low‐yield samples could provide sufficient material for microbiome analysis. We collected and analyzed, with amplicon metabarcoding, breath samples from managed care and free‐ranging killer whales (8 and 14 animals, respectively) and epidermal tissue from free‐ranging killer whales using dart biopsies and suction cups (11 and 30 animals, respectively). Exhaled breath aerosol from free‐ranging whales was distinct from seawater, but breath from managed care whales was not different from pool water. Eight bacterial species detected in breath from all managed care whales displayed elevated relative abundances in free‐ranging whales. Functional analysis revealed increased pathways associated with degradation and metabolism of xenobiotics and biosynthesis of terpenoid and polyketides in managed care whales. Epidermal collection method (biopsy vs. suction cups) produced differences in microbiomes but was still different from seawater microbiomes. Two bacterial species exhibited inverse abundance patterns between two resident killer whale populations. Epidermal microbiome functions were elevated for xenobiotic degradation and metabolism and for antimicrobial activities, consistent with constant exposure to marine environments. Evidence for the potential utility of these microbiomes for identifying whales with a poor survival prognosis was found for free‐ranging whales that were sampled within 6 months of presumed or known death. For at‐risk populations such as Southern Resident killer whales of the northeastern Pacific Ocean, microbiome analysis to help characterize individual animal health may contribute to safe and rational management decisions and policies.

Assessing the potential for building sector retrofits to mitigate ERCOT electricity shortfalls during Winter Storm Uri - Matthew J. Skiles; Justin Shih; Joshua D. Rhodes; Michael E. Webber (Energy and Buildings, 2025)

The Detroit volcanic province and the early evolution of the Hawaiian mantle plume - Reed B. Mershon; Aaron J. Pietruszka; Michael O. Garcia; Brian R. Jicha; Arron R. Steiner; Peng Jiang; J. Michael Rhodes; Michael J. Vollinger; Gregory F. Moore (Earth and Planetary Science Letters, 2025)

Do private land conservation policies and programs adequately consider climate change? - Yi Fei Chung; Martine Maron; Michael Drielsma; Jonathan R. Rhodes (Biological Conservation, 2025)

Designing modular, artificial reefs for both coastal defense and coral restoration - Benjamin K. Norris; Borja G. Reguero; Joseph Bartolai; Michael A. Yukish; Landolf Rhode-Barbarigos; Brian K. Haus; Gabriel Barajas Ojeda; Maria Maza; Javier L. Lara; Michael W. Beck (Coastal Engineering, 2025)

Ensuring reliability: What is the optimal time for power plant maintenance in Texas as the climate changes? - Hugh Daigle; Joshua D. Rhodes; Aidan Pyrcz; Michael E. Webber (The Electricity Journal, 2024)

Modern and prospective technologies for weather modification activities: A first demonstration of integrating autonomous uncrewed aircraft systems - T.P. DeFelice; D. Axisa; John J. Bird; C. Alexander Hirst; Eric W. Frew; R.P. Burger; D. Baumgardner; Gerhard Botha; Henno Havenga; Dan Breed; S. Bornstein; C. Choate; et al. (Atmospheric Research, 2023)

The influence of erosion and vegetation on soil production and chemical weathering rates in the Southern Alps, New Zealand - Isaac J. Larsen; Andre Eger; Peter C. Almond; Evan A. Thaler; J. Michael Rhodes; Günther Prasicek (Earth and Planetary Science Letters, 2023)

Perspectives on peak demand: How is ERCOT peak electric load evolving in the context of changing weather and heating electrification? - Matthew J. Skiles; Joshua D. Rhodes; Michael E. Webber (The Electricity Journal, 2023)

Risk factor determination and qualitative risk assessment of Mucormycosis in Harbor Porpoise, an emergent fungal disease in Salish Sea marine mammals - Stephanie A. Norman; Jessica L. Huggins; Dyanna M. Lambourn; Linda D. Rhodes; Michael M. Garner; Jennie L. Bolton; Joseph K. Gaydos; Alyssa Scott; Stephen Raverty; John Calambokidis (Frontiers in Marine Science, 2022)
Mucorales infections are increasing in frequency and are a One Health pathogen of concern. In humans and domestic animals, risk factors include being immunocompromised, elevated circulating serum iron, contaminated open wounds, or metabolic diseases such as ketoacidosis or uncontrolled diabetes. Mucormycosis was first identified in 2012 in Pacific Northwest marine mammals, predominantly in harbor porpoises. We performed an assessment to determine the overall qualitative risk, or risk score, of mucormycosis in harbor porpoises. Risk factors for this disease are unknown in aquatic mammals. In a separate risk factor analysis, potential risk factors such as pollutants, trace metals (e.g., iron), and co-infection with other pathogens (e.g., viruses and Brucella spp.) were examined in mucormycosis cases and noncases using a matched case-control study design, to determine the presence and strength of association of these factors with mucormycosis. Disease severity (gross and histopathology) and exposure scores were multiplied together to obtain the overall risk scores of 9 -16 which corresponded to moderate and severe, respectively. In the risk factor analysis, the factors most strongly associated with a mucormycosis case, relative to a control, were elevated liver iron, decreased blubber thickness, and the decreased ratio of the sum of PCB congeners/sum of PBDE congeners. The results of this study suggest that mucormycosis may pose an inordinately high risk to harbor porpoises (and potentially sympatric species in the Salish Sea such as southern resident killer whales) based on the detected prevalence and the severity of lesions observed at necropsy. However, the risk may be greater on an individual basis compared to the overall population, and is likely related to other factors such as increased POP and heavy metal burdens.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Azole‐resistant Aspergillus fumigatus is highly prevalent in the environment of Vietnam, with marked variability by land use type - Tra‐My N. Duong; Thanh‐Van Le; Khanh‐Linh H. Tran; Phuong‐Tuyen Nguyen; Bich‐Phuong T. Nguyen; Thu‐Anh Nguyen; Huong‐Lan P. Nguyen; Bich‐Ngoc T. Nguyen; Matthew C. Fisher; Johanna Rhodes; Guy Marks; Greg J. Fox; et al. (Environmental Microbiology, 2021)
Summary Azole‐resistant environmental Aspergillus fumigatus presents a threat to public health but the extent of this threat in Southeast Asia is poorly described. We conducted environmental surveillance in the Mekong Delta region of Vietnam, collecting air and ground samples across key land‐use types, and determined antifungal susceptibilities of Aspergillus section Fumigati (ASF) isolates and azole concentrations in soils. Of 119 ASF isolates, 55% were resistant (or non‐wild type) to itraconazole, 65% to posaconazole and 50% to voriconazole. Azole resistance was more frequent in A. fumigatus sensu stricto isolates (95%) than other ASF species (32%). Resistant isolates and agricultural azole residues were overrepresented in samples from cultivated land. cyp51A gene sequence analysis showed 38/56 resistant A. fumigatus sensu stricto isolates carried known resistance mutations, with TR 34 /L98H most frequent (34/38).

Accumulated Puʻu ʻŌʻō magma fed the voluminous 2018 rift eruption of Kīlauea Volcano: evidence from lava chemistry - Aaron J. Pietruszka; Michael O. Garcia; J. Michael Rhodes (Bulletin of Volcanology, 2021)

A bird's‐eye view of reservoirs in the Mississippi Basin tips a need for large‐scale coordination - Leandro E. Miranda; Giancarlo Coppola; Hunter R. Hatcher; Matthew B. Jargowsky; Zachary S. Moran; Michael C. Rhodes (Fish and Fisheries, 2021)
Reservoirs are mostly managed at local scales as spatially independent units. A basin‐scale perspective may increase awareness at a broader scope and generate insight not evident at local scales. We examined the array of reservoir attributes and fisheries in the Mississippi Basin to identify management opportunities. The basin is the third largest in the world and includes over 1,700 reservoirs >100 ha, the most of any river basin. Our bird's‐eye view shows a piecemeal approach where reservoirs are mostly administered at the local level. Basin‐wide or catchment coordination to holistically address problems that recur across the basin is mostly lacking. A basin‐wide coordination arrangement could facilitate various facets of reservoir management. We reviewed governance arrangements in major river basins across the globe and concluded that the basin‐wide administrative layer we encourage for the Mississippi Basin may already exist in some basins but may not be directly applicable everywhere.

The Emergence of Mucormycosis in Free-Ranging Marine Mammals of the Pacific Northwest - Jessica L. Huggins; Michael M. Garner; Stephen A. Raverty; Dyanna M. Lambourn; Stephanie A. Norman; Linda D. Rhodes; Joseph K. Gaydos; Jennifer K. Olson; Martin Haulena; M. Bradley Hanson (Frontiers in Marine Science, 2020)

Forecasting species range dynamics with process‐explicit models: matching methods to applications - Natalie J. Briscoe; Jane Elith; Roberto Salguero‐Gómez; José J. Lahoz‐Monfort; James S. Camac; Katherine M. Giljohann; Matthew H. Holden; Bronwyn A. Hradsky; Michael R. Kearney; Sean M. McMahon; Ben L. Phillips; Tracey J. Regan; et al. (Ecology Letters, 2019)
Knowing where species occur is fundamental to many ecological and environmental applications. Species distribution models (SDMs) are typically based on correlations between species occurrence data and environmental predictors, with ecological processes captured only implicitly. However, there is a growing interest in approaches that explicitly model processes such as physiology, dispersal, demography and biotic interactions. These models are believed to offer more robust predictions, particularly when extrapolating to novel conditions. Many process–explicit approaches are now available, but it is not clear how we can best draw on this expanded modelling toolbox to address ecological problems and inform management decisions. Here, we review a range of process–explicit models to determine their strengths and limitations, as well as their current use. Focusing on four common applications of SDMs – regulatory planning, extinction risk, climate refugia and invasive species – we then explore which models best meet management needs. We identify barriers to more widespread and effective use of process‐explicit models and outline how these might be overcome. As well as technical and data challenges, there is a pressing need for more thorough evaluation of model predictions to guide investment in method development and ensure the promise of these new approaches is fully realised.

Assemblage structure, vertical distributions and stable‐isotope compositions of anguilliform leptocephali in the Gulf of Mexico - Andrea M. Quattrini; Jennifer McClain‐Counts; Stephen J. Artabane; Adela Roa‐Varón; Tara C. McIver; Michael Rhode; Steve W. Ross (Journal of Fish Biology, 2019)
In August 2007, October 2008 and September–October 2010, 241 Tucker trawl and plankton net tows were conducted at the surface to depths of 1377 m at six locations in the northern and eastern Gulf of Mexico (GOM) to document leptocephalus diversity and determine how assemblage structure, larval size, abundance and isotopic signatures differ across the region and with depth. Overall, 2696 leptocephali representing 59 distinct taxa from 10 families were collected. Five families accounted for 96% of the total catch with Congridae and Ophichthidae being the most abundant. The top four most abundant species composed 59% of the total catch and included: Ariosoma balearicum , Paraconger caudilimbatus , Rhynchoconger flavus and Ophichthus gomesii . Four anguilliform species not previously documented in the GOM as adults or leptocephali were collected in this study, including Monopenchelys acuta , Quassiremus ascensionis , Saurenchelys stylura and one leptocephalus only known from its larval stage, Leptocephalus proboscideus . Leptocephalus catches were significantly greater at night than during the day. Catches at night were concentrated in the upper 200 m of the water column and significantly declined with increasing depth. Leptocephali abundances and assemblages were significantly different between sites on the upper continental slope ( c . 500 m depth) and sites on the middle to lower continental slope ( c . 1500–2300 m). Sites on the lower continental slope had a mixture of deep‐sea demersal, bathypelagic and coastal species, whereas upper‐slope sites contained several numerically dominant species ( e.g ., A. balearicum , P. caudilimbatus ) that probably spawn over the continental shelf and upper slope of the GOM. Standard lengths of the four dominant species differed between sites and years, indicating heterochronic reproduction and potential larval source pools within and outside of the GOM. Stable‐isotope analyses (δ 13 C and δ 15 N) conducted on 185 specimens from six families revealed that leptocephali had a wide range of isotopic values at the family and size‐class levels. Species in the families Muraenidae, Congridae and Ophichthidae had similar δ 15 N values compared with the broad range of δ 15 N values seen in the deep‐sea families Nemichthyidae, Nettastomatidae and Synaphobranchidae. Stable‐isotope values were variably related to length, with δ 15 N values being positively size correlated in ophichthids and δ 13 C values being negatively size correlated in A. balearicum and P. caudilimbatus . Results suggest that leptocephali feed in various water depths and masses, and on different components of POM, which could lead to niche partitioning. Ecological aspects of these important members of the plankton community provide insight into larval connectivity in the GOM as well as the early life history of Anguilliformes.

Factors influencing the adoption of riparian forest buffers in the Tuttle Creek Reservoir watershed of Kansas, USA - Thad K. Rhodes; Francisco X. Aguilar; Shibu Jose; Michael Gold (Agroforestry Systems, 2018)

Predicting species distributions for conservation decisions - Antoine Guisan; Reid Tingley; John B. Baumgartner; Ilona Naujokaitis‐Lewis; Patricia R. Sutcliffe; Ayesha I. T. Tulloch; Tracey J. Regan; Lluis Brotons; Eve McDonald‐Madden; Chrystal Mantyka‐Pringle; Tara G. Martin; Jonathan R. Rhodes; et al. (Ecology Letters, 2013)
Species distribution models (SDMs) are increasingly proposed to support conservation decision making. However, evidence of SDMs supporting solutions for on‐ground conservation problems is still scarce in the scientific literature. Here, we show that successful examples exist but are still largely hidden in the grey literature, and thus less accessible for analysis and learning. Furthermore, the decision framework within which SDMs are used is rarely made explicit. Using case studies from biological invasions, identification of critical habitats, reserve selection and translocation of endangered species, we propose that SDMs may be tailored to suit a range of decision‐making contexts when used within a structured and transparent decision‐making process. To construct appropriate SDMs to more effectively guide conservation actions, modellers need to better understand the decision process, and decision makers need to provide feedback to modellers regarding the actual use of SDMs to support conservation decisions. This could be facilitated by individuals or institutions playing the role of ‘translators’ between modellers and decision makers. We encourage species distribution modellers to get involved in real decision‐making processes that will benefit from their technical input; this strategy has the potential to better bridge theory and practice, and contribute to improve both scientific knowledge and conservation outcomes.

The Effect of Wind-Turbine Wakes on Summertime US Midwest Atmospheric Wind Profiles as Observed with Ground-Based Doppler Lidar - Michael E. Rhodes; Julie K. Lundquist (Boundary-Layer Meteorology, 2013)

Eleven microsatellite markers for the eastern gray squirrel (Sciurus carolinensis) and their utility in eastern fox squirrels (Sciurus niger) and red squirrels (Tamiasciurus hudsonicus) - Jennifer A. Fike; Cecilia A. Hennessy; Michael L. Kennedy; Olin E. Rhodes (Conservation Genetics Resources, 2013)

Impact of environmental conditions on the marine natural product bryostatin 1 - Thomas J. Manning; Emily Rhodes; Michael Land; Render Parkman; Brandy Sumner; TuKiet T. Lam; Alan G. Marshall¶; Dennis Phillips (Natural Product Research, 2006)

Petrology and geochronology of basalt breccia from the 1996 earthquake swarm of Loihi seamount, Hawaii: magmatic history of its 1996 eruption - Michael O. Garcia; Kenna H. Rubin; Marc D. Norman; J. Michael Rhodes; David W. Graham; David W. Muenow; Khalil Spencer (Bulletin of Volcanology, 1998)

Iron supplementation moderates but does not cure the Belgrade anemia - Michael Garrick; Donna Scott; Susannah Walpole; Eric Finkelstein; Joy Whitbred; Sandeep Chopra; Lalitha Trivikram; David Mayes; Daphne Rhodes; Kimberly Cabbagestalk; Rahmi Oklu; Adnan Sadiq; et al. (BioMetals, 1997)